Test-retest reliability of the questionnaire in the Sasang constitutional analysis tool (SCAT) - Jeongyun Lee; Mi Hong Yim; Jong Yeol Kim (Integrative Medicine Research)
Background: The Sasang constitutional analysis tool (SCAT) is an integrated Sasang constitutional analysis system developed by the Korea Institute of Oriental Medicine. This study aimed to evaluate the reliability of a questionnaire for measuring personality and pathophysiological symptoms that is one of the components of the SCAT. Methods: In this study, data were collected from university students in their twenties. Tests were administered twice, with an interval of 4 weeks between tests. Test-retest data from 176 students were collected and used for analysis. Internal consistency reliability was analyzed by using Cronbach's alpha coefficient, and test-retest reliability was analyzed by using Spearman's rank correlation coefficient. Results: Cronbach's alpha coefficient was 0.788 for personality, 0.511 for eating habits, 0.718 for digestion, 0.667 for heat- or cold-wise penchant, and 0.612 for water ingestion. Spearman's rank correlation coefficients, which were used to assess correlations between test and retest results, ranged from 0.444 to 0.828. Conclusion: The internal consistency and test-retest reliability of the SCAT questionnaire were found to be satisfactory. Keywords: Questionnaire, Sasang constitutional analysis tool (SCAT), Test-retest reliability, University students